2020
DOI: 10.3390/antiox9020166
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, Antimicrobial, Antioxidant Properties and Effects on Cell Migration of Phenolic Compounds of Selected Transylvanian Medicinal Plants

Abstract: Medicinal plants are widely used in folk medicine but quite often their composition and biological effects are hardly known. Our study aimed to analyze the composition, cytotoxicity, antimicrobial, antioxidant activity and cellular migration effects of Anthyllis vulneraria, Fuchsia magellanica, Fuchsia triphylla and Lysimachia nummularia used in the Romanian ethnomedicine for wounds. Liquid chromatography with mass spectrometry (LC-MS/MS) was used to analyze 50% (v/v) ethanolic and aqueous extracts of the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 74 publications
0
37
0
2
Order By: Relevance
“…Plant extracts are a valuable source of many bioactive substances that are responsible for their ability to increase the proliferation of keratinocytes and fibroblasts [ 54 ]. As Csepregi et al [ 55 ] have shown, many plants have proven properties to increase the viability and migration of skin cells. This action is one of the most important factors in the wound healing and prevention of skin aging processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant extracts are a valuable source of many bioactive substances that are responsible for their ability to increase the proliferation of keratinocytes and fibroblasts [ 54 ]. As Csepregi et al [ 55 ] have shown, many plants have proven properties to increase the viability and migration of skin cells. This action is one of the most important factors in the wound healing and prevention of skin aging processes.…”
Section: Resultsmentioning
confidence: 99%
“…This action is one of the most important factors in the wound healing and prevention of skin aging processes. Organic acids, polyphenols, flavonoids, vitamins and proteins are the main active ingredients of plants that are responsible for increase of proliferation of skin cells [ 55 , 56 ]. Among many active substances of plants, the strongest ability to improve the skin cells proliferation is shown by, e.g., caffeic acid and its derivatives, coumaric acid, gallic acid, rutin, quercetin and their derivatives [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. capsicoides and S. xanthocarpum, which were interchangeably used as the source of raw drug for many Ayurvedic preparations, can be attributed to the same properties as evidenced from the present study. Antioxidants also show antitumour, antimicrobial, and cytotoxic effects [51][52][53][54][55] . A study on the antioxidant potential in relation to total phenolics, flavonoids, anthocyanins and carotenoids was reported in the whole kernels of different wheat genotypes 56 .…”
Section: Discussionmentioning
confidence: 99%
“…However, because of more recent studies revealing interesting biological features like radical scavenging, antioxidative, astringent and antiviral activities in vitro , [8–10] the plant becomes increasingly interesting for the cosmetic and herbal industries [11] . Accordingly, extracts from A. vulneraria have been employed for several years in anthroposophic and herbal cosmetic remedies as functional ingredients [6]…”
Section: Introductionmentioning
confidence: 99%